Design and analysis of Yb doped ZnO (YZO) and P–Si bilayer nano-stacked reflector for optical filter applications. (October 2020) - Agarwal, Lucky; Singh, Richa; Varshney, Gaurav; SambasivaRao, K.; Tripathi, Shweta
Abstract: In the present paper, a multilayer stack of Yb doped ZnO (YZO) and p-Si has been designed in which the total internal reflection of optical light is combined to form constructive interference. The mechanism behind light propagation in a stack is revealed, and factors affecting the reflectivity of the stacked reflector are analytically investigated. In the visible range, an optimized reflectivity up to 99.3% is reached from two bilayer stacks. The thickness of stack layers is optimized to validate Fresnel's Law and the same has been further authenticated by the experimental results obtained from the ellipsometer. The device structure is numerically analyzed using the full wave simulator CST microwave studio. Furthermore, the reflector bands are linearly reconfigured by angular manipulation of the incident light. The experimental and simulated outcome of the multilayer stacked reflector shows the highest reflectivity of 99.3% for 550 nm wavelength of visible frequency spectrum. Highlights: A multilayer stacked structure has been prepared by an alternating layer of YZO and p-Si thin films. The prepared multilayer stacked reflector yields a high-reflection of greater than 98% at a wavelength of 520–680 nm. The TE and TM polarized wave is perfectly reflected at 550 nm wavelength for an angle of incident below 40°. The proposed act as a novel reflector to fabricate optical filter, which can be used for biomedical applications.